A new cicada species of Psalmocharias Kirkaldy feeding on an Ephedra plant from China (Hemiptera: Cicadidae) - Wang, Xu; He, Zhiqiang; Wei, Cong (Zootaxa, 2017)
A new species of the genus Psalmocharias Kirkaldy, 1908, P. akesensis sp. nov., from Xinjiang, China is described. A key to all species of Psalmocharias is provided. This new species feeds on the medicinal plant Ephedra intermedia Schrenk ex Mey, which contains various medicinally active alkaloids (notably ephedrine) and stimulates the central nervous system and influence muscle contraction of animals. The discovery of this new species may be informative for future studies of the detoxification mechanism in insects and for the protection of this important medicinal plant.